A study of the linguistic features of expressives in english vs vietnamese - Dương Thị Minh Mận (Trường Đại học Ngoại ngữ, 2025)
This thesis attempts to investigate the syntactic and semantic aspects of exclamative in contrastive analysis between English and Vietnamese. The data of the study were collected from many novels, short stories in English and Vietnamese . The data were then described on the syntax and semantics and showed that there are similarities and differences in both syntactic and semantic features of expressive in the two languages. The results have provided practical implications in language teaching and learning of expressives for English and Vietnamese users and learners.